Effect of heat and mass transfer on corrosion of carbon steel in a crude oil medium using corrosion inhibitors sodium nitrate and castor oil under different circumstances - Algburi, Abbas Kh. Ibrahim (Journal of Petroleum Research and Studies, 2022)
In the petroleum industry, corrosion is a fundamental problem that causes many operational and commercial problems, which require careful consideration and comprehensive studies in order to discover suitable solutions. Among these problems is the occurrence of corrosion in the crude oil production equipment as well as in the transportation pipelines of petroleum products, which leads to their failure; thus, increasing the cost as a result of maintenance or replacement. To protect them from corrosion, different types of inhibitors are commonly used, in which small amounts of inhibitor are continuously injected, slowly forming a thin layer of inhibitor between them and the corrosive materials to protect them from corrosion. In this study, the performance of the corrosion process was examined under varying temperatures, namely 20, 30, 40, 50 and 60 °C, at rotational speeds of 0, 500, 1250 and 2000 rpm. The concentrations of sodium nitrate (NaNO3) inhibitor were 0, 0.5, 1.0 and 1.5 g/l of crude oil, whereas the concentrations of castor oil inhibitor were 0, 0.5, 1.0 and 1.5 ml/l of crude oil. The results demonstrated that the corrosion rate of carbon steel in the crude oil decreases with the increase in the concentration of both types of inhibitors (NaNO3 and castor oil), while it increases with the rise in temperature and rotational speed. It was determined that the maximum efficiency of the green inhibitor (castor oil) in the crude oil was 93.7% at a concentration of 1.5 ml/l, temperature of 20 °C and a rotational speed of 0 rpm, while the maximum efficiency of the chemical inhibitor (NaNO3) in the crude oil was 98.6% at a concentration of 1.5 g/l, temperature of 20 ℃ and rotational speed of 0 rpm.